Development of costing model for butt joint process using mild steel with robotic GMAW: a Malaysian context / A. R. Ramlan ... [et al.] - Ramlan, A. R; Kassim, K.; Manurung, Y. H. P.; Prajadhiana, K. P.; Adenan, M. S.; Mat, M. F.; Busari, Y. O.; A. Rahman, A. R.; M. Ghazali, S. N. (UiTM Press, 2024)
This paper is about the development of a costing model aimed at determining the pricing strategy for a component manufactured through the welding process. Cost estimation in welding processes is crucial for industries due to various influencing factors like welding time, length, and joint type. Calculating welding costs involves considering various methods and factors. One method compares theoretical filling metal amounts with on-site welding material consumption, factoring in the welding difficulty coefficient. Additionally, Time Driven Activity Based Costing (TDABC) is one of the costing methods used to analyze input data and estimate welding costs accurately and efficiently, specifically in the GMAW process. Moreover, a comprehensive costing model developed by ESAB incorporates variables such as labor costs, electrode expenses, shielding gas usage, and overall power costs. In this paper, the selected welding design configuration is a double V- groove butt joint using mild steel, ER70S-3 as filler wire, and S235 mild steel as substrate. Based on the chosen design, the welding cost model will be developed to analyze the cost of the butt joint welding process based on time-driven activity-based costing (TDABC) method. The outcome of this study is the total cost to manufacture the Double V-Groove butt joint project in terms of materials, labor, and equipment. Furthermore, subsequent efforts will be directed toward systematically enhancing the welding cost model to include a broader spectrum of materials, various part dimensions, and differing deposition rates.